50 years of water extraction in the Pampa del Tamarugal basin: Can Prosopis tamarugo trees survive in the hyper-arid Atacama Desert (Northern Chile)?. (January 2016) - Chávez, R.O.; Clevers, J.G.P.W.; Decuyper, M.; de Bruin, S.; Herold, M.
Abstract: Groundwater-dependent ecosystems are threatened worldwide by unsustainable groundwater (GW) extraction. This is the case of the Prosopis tamarugo Phil forest in the hyper-arid Atacama Desert (Northern Chile), one of the most extreme ecosystems on Earth. Despite concerns about the conservation of this ecosystem, little research has been done to quantify the effects of the increasing GW depth (GWD) on the Tamarugo population. Here we provide a spatio-temporal assessment of the water condition of Tamarugo trees and propose GWD thresholds for their conservation. We studied spatio-temporal changes of GWD and the water status of the forest using Landsat images and hydrogeological records (1988–2013). This was complemented with a digital inventory and estimation of the green canopy fraction (GCF) of all trees using fine resolution satellite images. Since Tamarugos are solar trackers, their canopy spectral reflectance changes on a diurnal and seasonal basis. Thus, novel remote sensing drought stress indicators were defined: the mean NDVI in winter (NDVIW ) accounting for foliage loss and the NDVI difference between mean winter and summer (ΔNDVIW−S ) accounting for canopy water loss. NDVIW and ΔNDVIW−S of the Tamarugo forest declined on average 19% and 51%, respectively, while GW depleted on average 3 m over the period 1988–2013. About 730, 000 trees were identified in the study area, from which 5.2% showed a GCF < 0.25 associated with severe drought stress. A GWD > 12 m increasingly limited the paraheliotropic leaf movement, leading to dehydration and foliage loss. Tamarugos at 12–16 m GWD suffered moderate drought stress while GWD of 16–20 m implied severe drought stress. We suggest 20 m GWD as a critical threshold for the survival of Tamarugo trees. Highlights: Prosopis tamarugo, an endemic tree species of the Atacama Desert, is under threat. Groundwater extractions exceed by four times the natural recharge of the aquifer. We report on large scale spatio-temporal changes of the water status of the trees. Metrics sensitive to dehydration and defoliation decrease 51% and 19% respectively. Groundwater depth > 16 m increases drought stress, while 20 m is considered lethal.